MaltoKarpus Value Added Function Ingredient from Breadfruit through Thermo-Enzymatic Processing - Mohamed Zulkali, Mohamed Daud, Assoc. Prof. Dr.; Farizul Hafiz, Kasim; Noor Hasyierah, Mohd Salleh; Hafizah, Mohd Johar; Hafiza, Shukor; Sriyana, Abdullah; Rohazita, Johari (C. I. S. Network, 2010)
Assoc. Prof. Dr. Mohamed Zulkali Mohamed Daud and his team from School of Bioproses Engineering won gold for MaltoKarpus Value Added Function Ingredient from Breadfruit through Thermo-Enzymatic Processing. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.